2009
DOI: 10.3390/medicina45010005
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in the pediatric intensive care units in Lithuania

Abstract: Objective. The aim of the study was to collect the data on incidence rates, pathogens of nosocomial infections, and antimicrobials for treatment of nosocomial infections. Material and methods. Data were collected between March 2003 and December 2005 in five pediatric intensive care units using a modified patient-based HELICS protocol. Nosocomial infection was identified using the Centers for Disease Control definitions. All patients aged between 1 month and 18 years that stayed in the units for more than 48 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
27
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 32 publications
7
27
2
2
Order By: Relevance
“…3,4,6,[16][17][18]20,22,23 Similar to other developing countries VAP was most common HCAI in our study also. NHSN data for 2010 revealed a pooled mean of 1.2 VAP cases per 1000 ventilator-days.…”
Section: Site-specific/device-associated Infectionssupporting
confidence: 64%
See 2 more Smart Citations
“…3,4,6,[16][17][18]20,22,23 Similar to other developing countries VAP was most common HCAI in our study also. NHSN data for 2010 revealed a pooled mean of 1.2 VAP cases per 1000 ventilator-days.…”
Section: Site-specific/device-associated Infectionssupporting
confidence: 64%
“…(13.6-19.5%). 6,9,[16][17][18] The high incidence rates of HCAI in our PICU as in other developing countries could be multi factorial. Our hospital drains the area with poor standards of living.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the incidence of NIs was significantly higher in PICUs than in general wards in Western countries (3)(4)(5). In developing countries, NI rates of PICUs were reported as much higher (6)(7)(8). The distribution of infections by sites may vary with respect to various factors, such as age, properties of hospitals, the prevalence of invasive procedures, risk factors, and associated diseases of patients (3)(4)(5)8).…”
mentioning
confidence: 99%
“…One of the most important life-threatening medical problems of ICUs globally is NI (6) . Patients undergoing cardiovascular surgery had the highest hospital-acquired infection rate of 23 per 1000 patients.…”
Section: Discussionmentioning
confidence: 99%